Health seeking behaviour and knowledge on neonatal danger signs among neonatal caregivers in Upper Denkyira East Municipality, Ghana - Philip Gyaase; Edward Aduse-Poku; Mavis Opoku Lanquaye; Emmanuel Boateng Acheampong; David Ben Sampson (BMC Pediatrics, 2024)
Abstract Background The purpose of the project was to assess the health seeking behaviour and knowledge on neonatal danger signs among neonatal caregivers in Upper Denkyira East Municipality. Methods The study used a cross-sectional design and simple random sampling technique was employed to sample mothers’ neonates visiting the postnatal clinic in the selected health facilities. The target population was mothers with neonates and above 18 years visiting the health facilities and were willing to be part of the study. Total population for the study was 387 however, 381 responded to the questionnaire. Structured questionnaire was the main data collection tool for the study. Data were analysed with SPSS version 23.0. Logistic regression with Pearson Chi square, p-value and odd ratio were the main statistical methods for the data analysis. Results The results showed that 138 (36.2%) of the respondents stated that diarrhoea and vomiting constituted the major danger signs that sent their neonates to the hospital. Also the health seeking behaviour of the mothers showed positive results as most of the mothers (77.2%) attended hospital upon seeing neonatal danger sign. Finally, the association between mothers’ socio-demographic characteristics and recognition of neonatal danger signs showed that mothers educational level and occupation were statistically significant (p-value = 0.000). Conclusion The study concluded that mothers’ knowledge level on neonatal danger signs was high and also caregivers had good health seeking behaviour. It is recommended that community health nurses and midwives should embark on home visits to encourage mothers to practice the knowledge and skills acquired during counselling at the hospital. Mothers should be empowered to make decisions concerning their children’s health care.